Экспериментальное изучение биостатики грудных конечностей лошади во время отдыха - Клыков, В.И.; Манзий, С.Ф.; Мороз, В.Ф. (Вестник зоологии, 1974)
A new in principle idea of the essence of the horse rest in a standing position is arisen from the study of 3 clinically sound draught-horses by the methods of mechano- and electromyography. It is shown that each 1-27 min. thoracic limbs cease to be a support and make flexing-extensing movements in joints in turn. The authors consider that such character of the thoracic limb function in a horse at rest prevents a considerable deformation of the burdened tissues and ensures their normal hemodynamics.